Is the association between unhealthy weight and academic performance influenced by children’s physical activity level? - Carla Santana; Liane Azevedo; Lisianny Ferreira; Pedro Neves; Edna Prado; Wagner Prado (Revista Brasileira de Atividade Física e Saúde)
The purpose of this study was to verify the association between unhealthy weight and academic performance and the influence of physical activity level (PAL) in elementary school children. This study was conducted with 450 elementary school students (50% girls) enrolled in 1st to 4th grades. PAL was assessed by self-reported questionnaire of typical physical activity and daily food intake (DAFA). Academic achievement (Portuguese and Mathematics) was estimated based on the academic performance system of public schools from Recife/Brazil. Binary logistic regression was used to verify the association between unhealthy weight (underweight and overweight) and normal weight with academic performance. The results showed that 26.6% of the students presented overweight, 11.1% presented underweight, 49.1% and 50.9% were classified as high and low PAL, respectively. In addition, 56.9% had sufficient academic performance in Portuguese and 51.1% had sufficient academic performance in Mathematics. Students with overweight presented higher odds for insufficient  performance in Portuguese when compared to normal weight counterparts, even when adjusted for reported PAL, gender and age (OR = 1.69; 95%CI: 1.08-2.64). The results corroborate with evidences that unhealthy weight is associated with poor academic performance in children.